RECORD OF TWO ENDEMIC DAMSELFLIES FROM OBI ISLAND, MOLUCCAS, INDONESIA WITH HABITAT DESCRIPTION - Raja Rhamdany Harahap; Abdul Mutholib Shahroni (Treubia, 2024)
Obi Island as part of the Wallacea region has a variety of fauna with limited information such as Odonata taxa. In observations conducted in lowland secondary forests, two endemic damselflies were discovered, namely Argiolestes obiensis and Drepanosticta obiensis. Both species have habitat preferences for rocky streams with dense vegetation in the forest. In addition to habitat information, the first photograph of both species from the field was obtained in this study. This information is useful for data deficient species.